Absence of leptin resistance in platelets from morbidly obese individuals may contribute to the increased thrombosis risk in obesity - Dellas, Claudia; Schäfer, Katrin; Rohm, Ilonka; Lankeit, Mareike; Ellrott, Thomas; Faustin, Vivien; Riggert, Joachim; Hasenfuss, Gerd; Konstantinides, Stavros (Thrombosis and Haemostasis, 2008)
Clinical studies have shown that elevated leptin levels are an independent cardiovascular risk factor. However, little is known about the existence of platelet resistance to leptin in the setting of obesity. We examined the effects of leptin on platelet aggregation in morbidly obese subjects (n=40; BMI, 41.6 ± 1.1 kg/m2; leptin, 49.7 ± 3.4 ng/ml) in comparison to normal-weight controls (n=36; BMI, 23.3 ± 0.4 kg/m2; leptin, 6.5 ± 0.7 ng/ml).The aggregatory response to increasing concentrations of adenosine diphosphate (ADP) (2, 3, 4, and 5 µM) was significantly increased in platelets from obese compared to lean donors, reflecting a left shift in the dose-response curve. Plasma leptin levels, but not BMI, were significantly higher in subjects with stronger (above the median) compared to weaker (below the median) platelet aggregation at all ADP concentrations tested. In further experiments, stimulation (preincubation) with leptin (500 ng/ml) promoted ADP-induced platelet aggregation by approximately 25%, and there was no difference between platelets from obese and those from lean donors regarding the responsiveness to leptin (p=0.99). Western blotting revealed that leptin induced phosphorylation of JAK2 and STAT3 to a similar extent in platelets from both groups. Expression of potential mediators of leptin resistance (SOCS3 and PTP1B) also did not differ in platelets from obese and control subjects. In conclusion, our data indicate that platelets from obese donors show increased aggregatory response to ADP, and that this might partly be the consequence of increased circulating leptin levels. Platelets from obese donors are not resistant to the enhancing effects of leptin on ADPinduced platelet aggregation.
Keywords: Leptin; resistance; platelets; aggregation; obesity